Analisis Kebutuhan Sumber Belajar LMS Pada Mata Kuliah Micro Teaching - Pattaufi; Dedy Aswan (ILIN Institute Makassar, 2022)
The purpose of the study was to determine the needs of students in learning resources by using LMS in Micro Teaching courses. The research method is quantitative with research subjects Semester VI majors, Educational Technology UNM The instruments used in this research are questionnaires and interviews, the tendency shows that the presentation shows that 98% like online learning. The results of the questionnaire from the indicators of the need to pay attention to the tendency of 52.5% of students strongly agree, 47.1% agree if LMS learning media is developed using video. Besides video media, PPT media and books/ebooks also appear as options. Based on the results of this study, it can be concluded that it is necessary to develop LMS-based learning resources by combining more videos, followed by PPT and books/ebooks.